2019
DOI: 10.1002/eat.23006
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing the role of disgust in avoidant/restrictive food intake disorder: Implications for the etiology and treatment of selective eating

Abstract: Selective eating is a common presenting problem in Avoidant/Restrictive Food Intake Disorder (ARFID). Understanding the etiology of selective eating will lead to the creation of more effective treatments for this problem. Recent reports have linked disgust sensitivity to picky eating, and the field has yet to conceptualize the role that disgust might play in ARFID. Disgust has long been tied to formation of taste aversions and is considered at its core to be a food‐related emotion. A brief review of the litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 25 publications
2
15
1
1
Order By: Relevance
“…It has also been found that the medical and psychiatric comorbidities are greater in patients with ARFID than their AN counterparts (Becker et al., 2019; Bryson et al., 2018; Fisher et al., 2014; Lieberman et al., 2019; Norris et al., 2014). In psychiatric terms, higher rates of comorbidity in ARFID have been found with anxiety disorders, while in the case of AN, the higher rates are with mood disorders (Bryson et al., 2018; Cooney et al., 2018; Fisher et al., 2014; Katzman et al., 2019; Mammel & Ornstein, 2017; Menzel, Reilly, Luo, & Kaye, 2019; Nicely et al., 2014; Norris et al., 2014). Autism spectrum disorder (ASD), attention deficit hyperactivity disorder (ADHD), obsessive‐compulsive disorder (OCD), and learning disorders are more prevalent in ARFID than in AN (Beighley et al., 2013; Bryson et al., 2018; Coglan & Otasowie, 2019; Cooney et al., 2018; Eddy et al., 2015; Fisher et al., 2014; Katzman et al., 2019; J. Lucarelli et al., 2017; Nicely et al., 2014; Norris et al., 2014; Ornstein et al., 2017; Pennell et al., 2016; Thomas et al., 2017; Zimmerman & Fisher, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been found that the medical and psychiatric comorbidities are greater in patients with ARFID than their AN counterparts (Becker et al., 2019; Bryson et al., 2018; Fisher et al., 2014; Lieberman et al., 2019; Norris et al., 2014). In psychiatric terms, higher rates of comorbidity in ARFID have been found with anxiety disorders, while in the case of AN, the higher rates are with mood disorders (Bryson et al., 2018; Cooney et al., 2018; Fisher et al., 2014; Katzman et al., 2019; Mammel & Ornstein, 2017; Menzel, Reilly, Luo, & Kaye, 2019; Nicely et al., 2014; Norris et al., 2014). Autism spectrum disorder (ASD), attention deficit hyperactivity disorder (ADHD), obsessive‐compulsive disorder (OCD), and learning disorders are more prevalent in ARFID than in AN (Beighley et al., 2013; Bryson et al., 2018; Coglan & Otasowie, 2019; Cooney et al., 2018; Eddy et al., 2015; Fisher et al., 2014; Katzman et al., 2019; J. Lucarelli et al., 2017; Nicely et al., 2014; Norris et al., 2014; Ornstein et al., 2017; Pennell et al., 2016; Thomas et al., 2017; Zimmerman & Fisher, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Two recent studies revealed that the food-related emotion of disgust is related to ARFID symptoms9,10 and that patients with ARFID experienced disgust associated with their reaction to food, such as fear of vomiting or choking; therefore, patients with ARFID restrict their food intake, leading to one or more of the following: weight loss/growth faltering, nutritional deficiencies, supplement dependence, and psychosocial impairment (Box 1). 1 Thus, ARFID often obstructs the quality of daily activities, such as going to school or taking part in social activities.…”
Section: Introductionmentioning
confidence: 99%
“…One such paper by Katzman, Norris, and Zucker (), entitled “Avoidant/restrictive food intake disorder: first do no harm,” encourages clinicians to consider the potential negative consequences of nasogastric tube feeding for children and adolescents with ARFID. In another, Menzel, Reilly, Luo, and Kaye () hypothesize that selective eating in ARFID may be maintained by disgust specifically, and hypothesize that exposure‐based treatments, which are often used with ARFID but have been primarily been tested in other fear‐based disorders, may have limited efficacy for some individuals with ARFID.…”
Section: Novel Treatments For Arfidmentioning
confidence: 99%
“…One such paper by Katzman, Norris, and Zucker (2019), entitled "Avoidant/restrictive food intake disorder: first do no harm," encourages clinicians to consider the potential negative consequences of nasogastric tube feeding for children and adolescents with ARFID. In another, Menzel, Reilly, Luo, and Kaye (2019) hypothesize that selective eating in ARFID may be maintained by disgust specifically, and hypothesize that exposure-based treatments, which are often used with ARFID but have been primarily been appear to target the same underlying mechanism-non-acceptance of uncomfortable internal sensations-by helping patients learn to tolerate and accept distressing visceral (e.g., fullness) and emotional (e.g., disgust) sensations in order to increase food intake. If this mechanism is common across restrictive eating disorders, it could be an important transdiagnostic treatment target.…”
Section: Novel Treatments For Arfidmentioning
confidence: 99%